Pengaruh Penggunaan Aplikasi Quizizz Terhadap Minat Belajar Siswa Pada Mata Pelajaran PPKn Kelas X Di SMK Negeri 1 Omben Tahun Ajaran 2024/2025 - Moh. Ari Wibowo; Heni Adhianata; Rani Kuslinda; Linda Ramadhanty Januar (Jayapangus Press, 2026)
The condition of students' interest in learning Civic Education (PPKn) has declined, due to the limitations of the learning methods used in teaching. One effort that can be made is by using technology-based learning media, such as the Quizizz application. Previous research only focused on students' learning outcomes and motivation, whereas this study fills the gap by analyzing the effect of using the Quizizz application on students' interest in learning. This study aims to determine the effect of using the Quizizz application on students' interest in learning PPKn in grade X at SMKN 1 Omben. The research method used is a quantitative method with a quasi-experimental type. Data were collected through questionnaires and analyzed using an independent sample t-test. The results of the study indicate that there is a significant difference in students' interest in learning. This can be seen from the post-test scores obtained by the control class, which was 81,72, whereas the experimental class scored 105,78. This difference is also proven by the results of the independent sample t-test, which obtained a significance value (sig. 2-tailed) of 0.000 < 0.05, indicating that there is a significant difference between the class given the Quizizz application treatment and the class that was not given the treatment. Based on the research results, it can be concluded that Quizizz can be an effective learning medium for creating an enjoyable learning atmosphere. This study can serve as an evaluation for the use of Quizizz, suggesting that its application should be expanded not only to learning outcomes and motivation but also to learning interest as an affective variable.